2018
DOI: 10.1159/000490142
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of PTEN/PI3K/AKT Signaling Pathway in Shikonin-Induced Apoptosis and Proliferation Inhibition of Chronic Myeloid Leukemia

Abstract: Background/Aims: Chronic myeloid leukemia (CML) is a myeloproliferative neoplasm. Tyrosine kinase inhibitors (TKIs) are commonly used to treat CML; however, drug resistance of CML cells to TKIs has limited their clinical application. Shikonin, a traditional Chinese herb, has long been used to treat leukemia in China, but the roles and related molecular mechanisms of shikonin treatment in CML remain unclear. Here, we aimed to evaluate the effects of shikonin on the proliferation, apoptosis, and migration of K56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 47 publications
2
32
0
1
Order By: Relevance
“…Shikonin induces apoptosis and inhibits metastasis through suppressing ERK pathway in human NSCLC NCI-H460 and A549 cells, respectively [611,617]. c-Myc down-regulation along with inhibition of ERK/JNK/ MAPK and Akt pathways are also involved in shikonininduced apoptosis and anti-proliferation in acute and chronic leukemia [618][619][620]. Moreover, the activation of necroptosis initiators, receptor interacting serine-threonine protein kinase (RIP) 1 and RIP3, by shikonin does not only contribute to DNA double strand breaks via ROS overproduction [621], but also facilitates glycolysis suppression via intracellular H 2 O 2 production [622].…”
Section: Shikoninmentioning
confidence: 99%
“…Shikonin induces apoptosis and inhibits metastasis through suppressing ERK pathway in human NSCLC NCI-H460 and A549 cells, respectively [611,617]. c-Myc down-regulation along with inhibition of ERK/JNK/ MAPK and Akt pathways are also involved in shikonininduced apoptosis and anti-proliferation in acute and chronic leukemia [618][619][620]. Moreover, the activation of necroptosis initiators, receptor interacting serine-threonine protein kinase (RIP) 1 and RIP3, by shikonin does not only contribute to DNA double strand breaks via ROS overproduction [621], but also facilitates glycolysis suppression via intracellular H 2 O 2 production [622].…”
Section: Shikoninmentioning
confidence: 99%
“…Inducing autophagy is also one of the main mechanisms for anti-cancer activity 13,22,23 . Among them, PI3K and mTOR signalling pathways have been proved to be the main signal pathways to regulate autophagy [24][25][26][27] . However, for these kinds of derivatives, the poor selectivity and high cytotoxicity limit their clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…25 By regulating the PI3K/Akt signaling pathway, shikonin exerts anti-tumor effects in non-small cell lung cancer, chronic granulocyte leukemia, and Burkitt's lymphoma. [26][27][28] In the present study, we investigated the anti-tumor effects of SK in HCC cells. Our results showed that SK significantly inhibited HCC cell proliferation and glycolysis, and promoted HCC cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%